The Effectiveness of Solution-Based Couple Therapy on Communication Patterns and Emotion Control of Disturbed Women - Behbahani , Maryam; Zolfaghari , Maryam; Hobbi , Mohammadbagher (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to evaluate the effectiveness of solution-oriented couple therapy on improving communication patterns and emotional control of disturbed couples. Method: The present study was quasi-experimental with the experimental group, control, and pre-test, post-test with two-month follow-up. The statistical population of this study was 34 married women who were referred to Mehravar, Hamdelkadeh, Hamraz Zandegi, and Hamrah group counseling centers in Tehran in 2019. After screening using the Christensen and Solawai (1984) Couples Communication Patterns Questionnaire and Williams And Chambels (1997) Emotion Control Scale 24 women were selected and randomly assigned to the solution-based groups (12 women) and the control group (12 women). The experimental group received a weekly solution-based couple therapy intervention of McDonald (2007) as a group in 8 sessions of 90 minutes. Both groups were assessed in three stages of pre-test, post-test, and follow-up by the marital communication beliefs scale. Data were analyzed using repeated measures variance test. Results: The results showed that solution-based couple therapy has effect on adaptive constructive patterns (P = 0.005,F = 9.70), expectation / isolation (P = 0.047, F = 3.70), expectant man / isolation woman (P = 0.045, F = 4.51), expectant woman / isolation man (P = 0.014, F = 4.06), and adaptive avoidance (P = 0.006, F = 9.44) ; Also solution-oriented couple therapy is effective on controlling anger (P = 0.021, F = 6.16), controlling depressed mood (P = 0.004, F = 10.52), controlling anxiety (P=0.021, F=5.77) and positive emotion control (P = 0.027, F = 5.60) and this effect was stable in the follow-up phase (P